Compressive Strength by Incorporating Quarry Dust in Self-Compacting Concrete Grade M35 - Mushtaq Ahmad; Sana Ullah; Aneel Manan; Temple Chimuanya Odimegwu; Salmia Beddu (Salehan Institute of Higher Education, 2018)
The study has conducted to determine the workability and compressive strength of the self –compacting concrete. The sand has replaced with quarry dust with the proportion of 10, 20, 30 and 40% and super plasticizer was added 0.9%. The experiments were carried out at the Infrastructure University Kuala Lumpur (IUKL) concrete laboratory. Slump flow, J- Ring tests were carried out to determine the workability of self-compacting concrete and compressive strength test was conducted on 7 days and 28th days of curing period. A finding of the study shows that workability and compressive strength has increased by addition of quarry dust. It is concluded that addition of quarry dust up to 30% improve the workability of the self-compacting concrete and further addition of quarry dust decrease the workability. Additionally, compressive strength of the quarry dust modified self-compacting concrete shows the trend of higher compressive strength up to 30% addition of quarry dust with sand replacement and further addition decrease the compressive strength.